Driver's intention to use smartphone-car connectivity - Jieun Park; Junghwan Kim; Changi Nam; Seongcheol Kim (International Telecommunications Society (ITS), 2013)
Car is now more than just a transportation method. Now a smartphone or a portable device can be easily connected to your car and this allows us to enjoy broader range of contents like music and navigation. This study aims to study investigate what leads drivers to use such car-connectivity services. Based on the Unified Theory of Acceptance and Use of Technology (UTAUT) as theoretical framework, this study examines the relationship between four derived constructs (facilitating condition, technographics, mobile literacy, and prior similar experience) and behavioral intention to use car connectivity functionalities. The results show that two of them (facilitating condition and technographics) have significant impact on the intention to use car connectivity services but the other two (mobile literacy and prior similar experience) did not show statistically significant relationship with the behavioral intention.
Keywords: 330; Car connectivity; facilitating condition; technographics; intention to use new technology; the UTAUT